2021
DOI: 10.1111/1471-0528.17007
|View full text |Cite
|
Sign up to set email alerts
|

The role of confounding in the association between pregnancy complications and subsequent preterm birth: a cohort study

Abstract: Objective To estimate the degree of confounding necessary to explain the associations between complications in a first pregnancy and the subsequent risk of preterm birth.Design Population-based cohort study.Setting Western Australia.Population Women (n = 125 473) who gave birth to their first and second singleton children between 1998 and 2015.Main outcome measures Relative risk (RR) of a subsequent preterm birth (<37 weeks of gestation) with complications of preeclampsia, placental abruption, small-for-gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Na concentration in the umbilical cord showed a positive linear correlation with the duration of the pregnancy. A low level of Na (hyponatremia) is the most common electrolyte abnormality that may pose a risk to pregnancy [ 60 ] and contribute to pre-eclampsia, which can result in a shorter pregnancy [ 61 , 62 , 63 ]. Hsu et al [ 64 ] showed that hyponatremia in pre-eclampsia can lead to maternal respiratory and circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Na concentration in the umbilical cord showed a positive linear correlation with the duration of the pregnancy. A low level of Na (hyponatremia) is the most common electrolyte abnormality that may pose a risk to pregnancy [ 60 ] and contribute to pre-eclampsia, which can result in a shorter pregnancy [ 61 , 62 , 63 ]. Hsu et al [ 64 ] showed that hyponatremia in pre-eclampsia can lead to maternal respiratory and circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…High baseline PP at 12 to 19 weeks’ gestation has been demonstrated to be a risk factor for early spontaneous preterm birth in normotensive nulliparous women, and rises in SBP and DBP between baseline and mid-third trimester values associated with an increased risk of early and late spontaneous preterm births in a dose--response manner [ 31 ] especially in women with obesity [ 32 ]. A plausible mechanism for this finding is that raised hypertensive indices increase preeclampsia risk: term preeclampsia in a first pregnancy is a major risk factor for subsequent preterm birth with or without recurrent preeclampsia [ 33 ]. Overall, elevated SBP and PP should alert clinicians to the possibility of pregnancies at a higher risk of preterm delivery and trigger appropriate peripartum care.…”
Section: Discussionmentioning
confidence: 99%
“…The association between preterm birth and prenatal cannabis use may also be due to a range of risk factors such as hypertensive disorders of pregnancy and gestational diabetes [61,62]. Evidence from an epidemiological study has suggested that the risk of preterm birth due to gestational diabetes may be higher if pregnant women develop diabetes prior to the 24th week of gestation [62].…”
Section: Discussionmentioning
confidence: 99%